Endoscopic findings in the soft palatal mucosa are associated with the risk of esophageal squamous cell carcinoma. Issue 5 (29th October 2020) - Waki, Kotaro; Ishihara, Ryu; Maekawa, Akira; Inoue, Takahiro; Shoji, Ayaka; Matsueda, Katunori; Miyake, Muneaki; Fukuda, Hiromu; Shichijo, Satoki; Kanesaka, Takashi; Takeuchi, Yoji; Higashino, Koji; et al.
Abstract: Background and Aim: We investigated endoscopic findings of the soft palatal mucosa to identify factors associated with esophageal squamous cell carcinoma (ESCC). Methods: This study was conducted during endoscopic examinations of subjects at Osaka International Cancer Institute from January 2020 through May 2020. We took endoscopic images of the soft palate under non‐magnifying and mild‐magnifying observations. Subjects with ESCC or a history of ESCC were defined as the ESCC group. Two endoscopists who were blinded to subjects' clinical information interpreted 10 endoscopic findings: melanosis, brownish changes, whitish epithelium, vasodilation, circular alignment of dilated vessels, uneven surface, uneven epithelial color, uneven vessel visibility, palate ridge, and erosion. Subjects were interviewed about their alcohol use, smoking, and flushing reactions. Results: Two hundred eighty‐two subjects, including 151 in the ESCC group and 131 in the non‐ESCC group, were included in the analysis. Univariate analyses and multivariate logistic regression demonstrated that melanosis, whitish epithelium, and vasodilation were significantly associated with ESCC. The positive likelihood ratios (PLRs) of melanosis, whitish epithelium, and vasodilation were 3.3, 4.2, and 2.8, respectively. Additionally, the PLRs for three of the endoscopic findings in subjects with drinking and smoking habits were higher than in those without these habits—PLRs ranging from 7.23 to 19.1. High PLRs for three endoscopic findings suggested a high possibility of ESCC. Interobserver agreement was substantial for whitish epithelium, moderate for melanosis, and fair for vasodilation. Conclusions: Three endoscopic findings in soft palate were considered to be useful as alarming signs that indicate ESCC risk.